HUBUNGAN KONSUMSI SAYUR DAN BUAH DENGAN RISIKO OBESITAS PADA REMAJA DI SMP NEGERI 174 JAKARTA - Nurul Septianti (2022)
Obesity is a condition of the body that has excessive or abnormal fat accumulation and can increase the risk to health. Adolescents have a risk of obesity that may occur into adulthood. Obesity that occurs in the adolescent age group is also due to having low fiber intake. This study aims to determine the relationship between consumption of vegetables and fruit with the risk of obesity in adolescents at SMP Negeri 174 Jakarta. The method used is an observational quantitative research with analytic design and using a cross sectional study approach. The sample used amounted to 157 samples obtained through multistage sampling technique, the first stage using purposive sampling and then followed by simple random sampling technique. Measurements were made by measuring height and weight and filling out a questionnaire using a structured instrument. The results of the analysis with the chi square test showed that there was a relationship between consumption of vegetables and fruits with the risk of obesity in adolescents with p value = 0.026 (<0.05). It is hoped that teenagers will pay more attention to the nutrients contained in the food they eat.